Agência Lupa, facebook e consumo de notícias: análises sobre a desinformação na pandemia da Covid-19 - Deodato, Paulo Gerson Olinto (2022)
We live in the age of disinformation, in which false content spreads across the internet in a matter of seconds, negatively influencing the functioning of society. Thus, not only is democracy put at risk, but also the health of populations around the world. Despite being on the rise, this false information has been harming humanity for a long time, well before new technologies came along. In this sense, this research highlights the impacts caused by disinformation on society and also the relevance of the work of the checking agencies in the fight against false information. The study is aimed at Lupa due to its prominence in actions against disinformation both nationally and internationally, and false information is the object of analysis for delaying the end of the pandemic. First, this research analyzes the main false information that circulated between March 10 and May 10, 2020, that is, in the first two months of the pandemic counting from the date that the World Health Organization (WHO) declared a global pandemic. The survey also highlights the results of an online questionnaire applied to the public on news consumption, which obtained 103 responses. The objective is to understand how the forms of consumption were modified in this period and how the public reacts to this excessive amount of information. Another analysis from the anti-vaccine Facebook group called “The dark side of vaccines” is presented. The data collected on the Lupa website and the Facebook group are categorized using a diagram, based on Bardin's studies on content analysis (2011). The 193 checks studied on the Lupa website show that homemade recipes to cure Covid-19 are the false information that most convinces the population. In addition, consumers of this information, whether false or true, report characteristics of anxiety, depression, panic, and even feel the need to distance themselves from news related to the pandemic. In the anti-vaccine group studied, we noticed that there is a considerable amount of false content that tries to discredit science and vaccination. There are more than 15 thousand members in the group, interacting and trying to find ways to escape the mandatory immunization. We also conclude that the end of the pandemic is further away with the circulation of false information, which causes negative psychological impacts on the population. Checking agencies do not solve the problem of disinformation alone, which is why it is important to combine media education, effective laws and fact checking. These checks also do not reach all audiences, considering that these texts are read by people with a higher educational level, excluding people with a low level of education. Finally, we present data that show the urgency of actions that seek to minimize the impacts of misinformation on society, since they can have serious consequences.